WMAP 5-year constraints on time variation of α and me in a detailed recombination scenario - Scóccola, C.G. (2008)
We study the role of fundamental constants in an updated recombination scenario. We focus on the time variation of the fine structure constant α, and the electron mass me in the early Universe, and put bounds on these quantities by using data from CMB including WMAP 5-yr release and the 2dFGRS power spectrum. We analyze how the constraints are modified when changing the recombination scenario. © 2008 Elsevier B.V. All rights reserved.